Raman memory for entanglement in diamonds and light storage in optical fibres - Sprague, M (2014)
Light, when reduced to the level of individual quanta, can possess, besides its familiar properties of wavelength, direction, and polarization, a set of correlations irreducible to classical correlations, among other peculiar behaviour. These correlated states are intrinsically interesting, and are also useful for quantum-enhanced information processing. In this thesis, I use a high-bandwidth, far-off-resonant Raman memory to implement two quantum information primitives -- entanglement generation and light storage -- at room temperature and ambient conditions. Specifically, I show, for the first time, the entanglement of two solid-state objects at room temperature and, also, the storage of light in a hollow-core optical fibre. In the first part, I show that the optical phonon modes of two diamonds can be entangled -- the prototypical non-classical correlation -- at room temperature. The entanglement was generated by spontaneous Raman scattering with projective measurements using single-photon detectors. The degree of entanglement was rigorously quantified by measuring the concurrence -- an entanglement monotone -- of the joint state of the scattered optical fields. In the second part, I store light in the coherent superposition of cesium atoms confined within a kagome-structured hollow-core photonic crystal fibre at room temperature using a far-off-resonant stimulated Raman interaction. The storage efficiency of the memory was 27$pm$1% and the noise level was sufficiently low such that single-photon-level pulses could be stored. Taken together, these results highlight the potential of Raman memories for quantum information tasks in noisy systems with short coherence times.